Evaluation of blood processed by cell saver in pediatric scoliosis - García, Elena; Rey, Pilar del; Martínez, Ernesto (Jour Med Resh and Health Sci, 2020)
Introduction:We study the hematological and microbiological characteristics from the autologous blood processed through the intraoperative cell saver used in our centre (Orthopat®) during the correction of pediatric scoliosis, which is known to be a potentially bleeding surgery. Material and methods: Descriptive analysis of 31 patients undergoing pediatric scoliosis surgery. All of them received blood processed by cell saver intraoperatively. The variables collected were: demographic data, volume of the autogenous red blood cell (RBC) concentrate, blood count, biochemistry, blood culture, preoperative and postoperative blood tests of the patients, incidence of fever during reinfusion of RBC concentrate, postoperative surgical site infections and length of hospital stay. Results: Average volume obtained 288.06ml (sd 154.68). Hematocrit 70.38% (sd 10.03) in accordance with cell-saver commercial data (75%). Of the blood samples obtained, 42.86% had blood cultures that were positive for aerobes and 48.28% for anaerobes. The relation between postoperative infections and contamination of blood concentrates was not statistically significant. When comparing the pre-surgery and post-surgery analytical samples, statistically significant differences (p <0.05) were found in the following: hemoglobin and hematocrit decreased in the postoperative period, while coagulation parameters show a tendency to coagulopathy. Conclusion: Our cell saver obtains RBC concentrates with a percentage of hematocrit in agreement with available information. The reinfusion of them is safe from an infectious and biochemical point of view, but its immunological implications are not clear. This surgery continues to result in a significant loss of blood. Measures taken to avoid allogenic transfusions remain necessary and should be enhanced.